2001
DOI: 10.1046/j.1523-1755.2001.0590062095.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin suppresses oxidative stress and fibrosis in the interstitium of mouse kidneys with unilateral ureteral obstruction

Abstract: These results provide evidence for the antioxidant action of fluvastatin in vivo. The decreased interstitial fibrosis along with a decreased oxidative stress marker in the interstitial lesion strongly suggests the existence of a causal relationship between them. Fluvastatin may have therapeutic value in slowing or preventing interstitial fibrosis in progressive renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
39
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…10,29 As oxidative stress has been implicated in the pathophysiology of chronic pancreatitis 30,31 and antioxidant treatment can inhibit TGF-b release and thereby suppress pancreatic inflammation and fibrosis, 32 it is conceivable that pravastatin suppresses progression of pancreatic inflammation and fibrosis in this experimental model by attenuating oxidative stress. In support of our view, previous studies have shown that statins reduce fibrosis and inflammation along with an attenuation of oxidative stress in the kidney 4 and heart. 33 In this study, we found that treatment with pravastatin markedly increased production of IL-10 in the pancreas.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…10,29 As oxidative stress has been implicated in the pathophysiology of chronic pancreatitis 30,31 and antioxidant treatment can inhibit TGF-b release and thereby suppress pancreatic inflammation and fibrosis, 32 it is conceivable that pravastatin suppresses progression of pancreatic inflammation and fibrosis in this experimental model by attenuating oxidative stress. In support of our view, previous studies have shown that statins reduce fibrosis and inflammation along with an attenuation of oxidative stress in the kidney 4 and heart. 33 In this study, we found that treatment with pravastatin markedly increased production of IL-10 in the pancreas.…”
Section: Discussionsupporting
confidence: 90%
“…1 Therefore, statins are widely used in the first-line management of hyperlipidemia due to their efficacy in improving plasma lipid profiles. 1 However, as mevalonate is the precursor not only of cholesterol, but also of many non-steroidal compounds, inhibition of HMG-CoA by statins may result in pleiotropic effects such as anti-inflammatory, 2 anti-fibrotic 3 and antioxidative 4 actions.…”
mentioning
confidence: 99%
“…Inhibitors of hydroxymethylglutaryl-coenzyme A reductase such as statins, which are widely used to lower serum cholesterol, have been shown to reduce the progression of renal fibrosis and glomerulosclerosis upon unilateral urethral obstruction (34). Furthermore, statins prevented cardiac fibrosis in rabbits transgenic for ␤-myosin heavy-chain Q(403), a common model of hypertrophic cardiomyopathy (35).…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of an anti-oxidant enzyme catalase enhanced tubulointerstitial injury and fibrosis in UUO in mice (43). On the other hand, anti-oxidant agents, such fluvastatin and bioflavonoids, inhibited renal fibrosis in UUO (15,28). Therefore, anti-oxidant actions may represent one plausible mechanism by which CO inhibits renal tubulointerstitial fibrosis in UUO.…”
Section: Discussionmentioning
confidence: 99%